Trust and Reflection in Primary Care Practice Redesign. (27th November 2015) - Lanham, Holly Jordan; Palmer, Raymond F.; Leykum, Luci K.; McDaniel, Reuben R.; Nutting, Paul A.; Stange, Kurt C.; Crabtree, Benjamin F.; Miller, William L.; Jaén, Carlos Roberto
Abstract : Objective: To test a conceptual model of relationships, reflection, sensemaking, and learning in primary care practices transitioning to patient‐centered medical homes (PCMH). Data Sources/Study Setting: Primary data were collected as part of the American Academy of Family Physicians' National Demonstration Project of the PCMH. Study Design: We conducted a cross‐sectional survey of clinicians and staff from 36 family medicine practices across the United States. Surveys measured seven characteristics of practice relationships (trust, diversity, mindfulness, heedful interrelation, respectful interaction, social/task relatedness, and rich and lean communication) and three organizational attributes (reflection, sensemaking, and learning) of practices. Data Collection/Extraction Methods: We surveyed 396 clinicians and practice staff. We performed a multigroup path analysis of the data. Parameter estimates were calculated using a Bayesian estimation method. Principal Findings: Trust and reflection were important in explaining the characteristics of practice relationships and their associations with sensemaking and learning. The strongest associations between relationships, sensemaking, and learning were found under conditions of high trust and reflection. The weakest associations were found under conditions of low trust and reflection. Conclusions: Trust and reflection appear to play a key role in moderating relationships, sensemaking, and learning in practices undergoing practice redesign.